1998
DOI: 10.1007/bf02468502
|View full text |Cite
|
Sign up to set email alerts
|

Phase transformations in heat treatment of Al−Li alloys and optimization of operational properties of semifinished products from these alloys

Abstract: In recent years AI -Li alloys have become very popular in the aircraft industry. These alloys are characterized by a high specific strength and rigidity which increases substantially the load ratio and fuel efficiency of the parts. As a rule, Al -Li alloys are used in an underaged state, which provides a high ductility over the height of the semifinished products. However, the threshold stress (Ocr) in corrosion cracking in this state does not usually exceed 25 -50 N/ram 2, and the yield strength is not always… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 1 publication
1
19
0
Order By: Relevance
“…This concept agrees well with the data of differential scanning calorimetry (DSC) of aluminum alloys. The scheme (succession) of the decomposition of the solid solution presented in [16] is implementable under industrial conditions, has been confirmed by the results of transmission electron microscopy, x-ray phase analysis, and differential scanning calorimetry, and agrees well with the thermokinetic diagrams [9,12,13,16,17]. The presented series of phase transformations are realized in actual heat treatment of a wide range of commercial stamped preforms from alloy 1420.…”
Section: Continuous Decomposition Of the Solid Solution In Hardening supporting
confidence: 65%
See 2 more Smart Citations
“…This concept agrees well with the data of differential scanning calorimetry (DSC) of aluminum alloys. The scheme (succession) of the decomposition of the solid solution presented in [16] is implementable under industrial conditions, has been confirmed by the results of transmission electron microscopy, x-ray phase analysis, and differential scanning calorimetry, and agrees well with the thermokinetic diagrams [9,12,13,16,17]. The presented series of phase transformations are realized in actual heat treatment of a wide range of commercial stamped preforms from alloy 1420.…”
Section: Continuous Decomposition Of the Solid Solution In Hardening supporting
confidence: 65%
“…At the present time we have developed a regime TV2 for full-scale treatment that removes all the defects and provides a higher operational reliability than regime TVI [8]. This is connected predominantly with the 8' --* 8 phase transformation in aging and the reduction of the supersaturation of the solid solution with lithium [8,16]. This effect is especially well manifested in alloys with a high lithium content (2.0-2.5%).…”
Section: Phase Transformations In Continuous Cooling Of Commercial Sementioning
confidence: 91%
See 1 more Smart Citation
“…of the mechanical properties, the crack resistance, and the corrosion resistance in alloy 1420 [9,10]. Further reduction of the volume fraction of the 5'-phase and growth of the content of the &phase occur after a stabilizing aging which, as has been shown in [15,23,24], considerably increases the corrosion resistance of aluminum-lithium alloys. The stabilizing aging (regime TV2 for alloy 1420) accompanied by segregation of a &phase considerably compensates for the decrease in ~cr in the repeated heating and reduces the residual stresses even more than regime TVI (by 65 -70%).…”
Section: Results and Their Discussionmentioning
confidence: 97%
“…It seems that the low thermal stability of aluminum-nickel alloys can have a negative effect on the anisotropy of ~d-/c [6] and on crc~ [15], which finally increases the susceptibility of the material to delayed fracture. In this connection it is desirable to devote more attention to the study of the thermal stability.…”
Section: Results and Their Discussionmentioning
confidence: 97%